CCL2 serves as a downstream effector of interleukin‐1β and tumour necrosis factor‐α signalling in Schnitzler syndrome. (1st April 2019) - Kambe, N.; Nguyen, C. T. H.
Abstract: Linked Article : Krause et al. Br J Dermatol 2019; 180 :859–868 .